Safety and immunogenicity of single-dose live oral cholera vaccine strain CVD 103-HgR in healthy adults age 18–45. Issue 6 (1st February 2018) - McCarty, James M.; Lock, Michael D.; Hunt, Kristin M.; Simon, Jakub K.; Gurwith, Marc
Highlights: Phase 3 live, oral cholera vaccine CVD 103-HgR study in adults age 18–45. Measured safety, immunogenicity, lot consistency; most reactogenicity mild. Serum vibriocidal antibody seroconversion rate was 94% 10 days after vaccination. Vibriocidal antibodies persisted above baseline through 6 months post-vaccination. Immunogenicity and safety endpoints were equivalent between three production lots. Abstract: The attenuated recombinant Vibrio cholerae O1 vaccine strain CVD 103-HgR, re-developed as PXVX0200, elicits a rapid serum vibriocidal antibody (SVA) response and protects against cholera diarrhea in volunteer challenge studies. We performed a phase 3, placebo controlled, double blind, multi-center study to further assess the safety, immunogenicity, and lot-to-lot consistency of PXVX0200. Adult volunteers 18–45 years of age were randomized 8:1 to receive a single dose of 1 × 10 9 CFU of PXVX0200 from three production lots or saline placebo. Immunogenicity endpoints included SVA and anti-cholera toxin (CT) antibody levels on days 1, 11, 29, 91 and 181. Safety was assessed by comparing solicited signs and symptoms on days 1–8, unsolicited adverse events through day 29 and serious adverse events through day 181. A total of 3146 participants were enrolled, including 2795 vaccine and 351 placebo recipients. The SVA seroconversion rates at day 11 were 94% and 4% in the PXVX0200 and placebo recipients, respectively (P < .0001). Cumulative SVA seroconversion occurred among 96% of vaccine recipients. PXVX0200 SVA GMTs peaked on day 11 and remained significantly higher than placebo through day 181 while the fold-rise over baseline in PXVX0200 anti-CT antibody was significantly greater than placebo at every post-vaccination time point. Most reactogenicity was mild and resolved within 1–3 days with headache and diarrhea more frequently reported in PXVX0200 recipients. There were no differences in unsolicited adverse events and no study-related serious adverse events. Immunogenicity and safety endpoints were equivalent between the three production lots. PXVX0200 is immunogenic and well tolerated across multiple production lots. Clinical Trials Registration: Clinicaltrials.gov NCT02094586.